Peran Guru PPKN Dalam Menanggulangi Kenakalan Remaja Di SMK Negeri 1 Biau Kabupaten Buol - Lucyane Djafaar; Asmun W Wantu; Serina Rahmat (Departement of Mathematics Education, 2024)
This research discusses the role of PPKn teachers in tackling juvenile delinquency at SMK Negeri 1 Biau, Buol Regency. By using qualitative research with a descriptive approach, this is done to obtain research data in accordance with the conditions that occur in the field because the data is obtained through observation, interviews and documentation in order to strengthen the research data. The results of research on the role of PPKn teachers in dealing with juvenile delinquency at SMK Negeri 1 Biau, Buol Regency, seen from the aspect of teachers as guides and teachers as moral agents, have gone well in accordance with their duties and responsibilities as teachers who guide students' morals. Meanwhile, the factors that influence the occurrence of juvenile delinquency are caused by internal factors and external factors. Where lack of self-awareness, weak self-control and lack of parental attention, free association, social media, social environment causes juvenile delinquency.